The role of artificial intelligent in streamlining assurance and supervision procedures for CVC Finance Limited - Salman, Md. Mostafa (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.